Evaluasi Program - Program Strategis Pemerintah Kota Bandung Di Bidang Ekonomi dalam Upaya Penguatan dan Peningkatan Kemampuan Daya Beli Masyarakat : Suatu Tinjauan Analisis Kebijakan Publik - Bayu Kharisma (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
This study aims to evaluate and prioritize the various forms of strategic programs at the Bandung City Government in strengthening the economy and increasing purchasing power of the people in the city of Bandung based on public policy analysis. This study is comprehensive covering macro aspects, namely the potential and economic profile as well as the Human Development Index (HDI) and micro aspects, namely the external and internal environmental analysis relating to economic policy on purchasing power. Furthermore, evaluation and economic policy priorities in an effort to increase the purchasing power of the city of Bandung. There are few steps or effort in evaluating various forms of local government strategic program Bandung in economics in order to increase the purchasing power of the city of Bandung, namely: 1) Observing the potential and the problems by SWOT analysis (strengths, weaknesses, opportunities, threats). 2) Evaluation and prioritization of programs of economic analysis AHP (analytical hierarchy process) and connect it to the macroeconomic indicators Bandung. In conducting the evaluation and priority, strategic programs are done also based on the study of literature and discussions with experts. The number of respondents in this study is 15 (fifteen) and sampling was done by purposive convenience sampling. Based Matrix EFAS (External Strategic Factors Analysis Summary) shows that the Bandung City Government is in a strong position to exploit the opportunities that exist to minimize the threats that will arise with regard to the external factors that affect the purchasing power of the city of Bandung. The Government of Bandung can utilize the opportunities, which are significant factors, in order to increase the purchasing power of the people. These are plans such as: the Central Government Policies Regarding Rice for the Poor (RASKIN), Health Insurance for the Poor (insurance for the poor), and the School Operational Assistance (BOS), National Program Community Empowerment (PNPM), the People's Business Credit (KUR) with Interest Subsidy to Help Low Income Communities . Furthermore, from the results of Matrix IFAS (Internal Strategic Factor Analysis Summary) shows that the Bandung City Government is in a relatively strong position to use and harness the forces that exist to minimize the shortcomings encountered in efforts to improve the people's purchasing power. Internal factors that significantly influence the increase in purchasing power of the city of Bandung are the strong commitment of the Government of Bandung to increase purchasing power. Meanwhile, the biggest disadvantage factor and should be watched and minimized by the Bandung City Government in improving the purchasing power of the city of Bandung is a "Weak Monitoring and Evaluation Capability Strengthening Program Buy". The estimation results of AHP (analytical hierarchy process) to local agencies regarding the analysis of preference evaluation of Government programs of Bandung in economics in improving and strengthening the purchasing power suggests that external factors are the priority aspects. Meanwhile, based on analysis of the preferences of businesses, communities and government agencies to the actors who play an important role in strengthening the purchasing power of the city of Bandung show that the relevant local government agencies play an important role in influencing people's purchasing power state through a set of policies and programs it has taken.